Kontribusi Stresor dan Motivasi Kerja terhadap Kinerja Tenaga Kependidikan Berdasarkan Uraian Tugasnya di Institusi Pendidikan Kesehatan Karya Husada Kediri (Sebuah Analisis Jalur) - Wahyu Nuraisya; Firman F. Wirakusumah; Tina Dewi Judistiani (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2013)
Background: Quality of management education is an important aspect for the continuity of education and the acquisition of quality outcomes. Human resource management requires good performance of educational personnel in providing services to students and the lecturers themselves supporting the implementation of tasks. For the lecturers, the demand of task implementation is sort of a stressor. A good motivation well-achieved the performance of educational personnel. This study aimed to determine the correlation of stressors and motivation of the lecturers’ performance based on job descriptions in the work of health education institution Karya Husada Kediri.Method: This study is an analytical research correlated with cross-sectional approach. The population is all educational personnel in health education institution Karya Husada Kediri. Study sample was 50 educational staff with a total population of the technique. Collecting date using questionnaire.Results: The results of correlation analysis using Pearson test found that work stressors negatively correlated (r = -0.315) with the performance, and there is a positive correlation (r = 0.408) between work motivation and performance. The results of analysis using path analysis showed a influence between stressors and simultaneously with the performance of work motivation with square values of r = 0.359 and the influence of other variables that are not observed at 0.641.Conclusion: Low work stressors and highly motivation could raise the performance of the educational personnel at health education institute Karya Husada Kediri so in that way there is much more thing to do how to deal with work stressors and motivational improvement to gain better performance.